Novel Angiogenic Regulators and Anti-Angiogenesis Drugs Targeting Angiogenesis Signaling Pathways: Perspectives for Targeting Angiogenesis in Lung Cancer - Li, Yingying; Lin, Mengmeng; Wang, Shiyuan; Cao, Bo; Li, Chunyu; Li, Guohui (Frontiers in Oncology, 2022)
Lung cancer growth is dependent on angiogenesis. In recent years, angiogenesis inhibitors have attracted more and more attention as potential lung cancer treatments. Current anti-angiogenic drugs targeting VEGF or receptor tyrosine kinases mainly inhibit tumor growth by reducing angiogenesis and blocking the energy supply of lung cancer cells. However, these drugs have limited efficiency, raising concerns about limited scope of action and mechanisms of patient resistance to existing drugs. Therefore, current basic research on angiogenic regulators has focused more on screening carcinogenic/anticancer genes, miRNAs, lncRNAs, proteins and other biomolecules capable of regulating the expression of specific targets in angiogenesis signaling pathways. In addition, new uses for existing drugs and new drug delivery systems have received increasing attention. In our article, we analyze the application status and research hotspots of angiogenesis inhibitors in lung cancer treatment as a reference for subsequent mechanistic research and drug development.